Engineered hapten‐binding antibody derivatives for modulation of pharmacokinetic properties of small molecules and targeted payload delivery. Issue 1 (March 2016) - Dengl, Stefan; Sustmann, Claudio; Brinkmann, Ulrich
Summary: Hapten‐binding antibodies have for more than 50 years played a pivotal role in immunology, paving the way to antibody generation (as haptens are very important and robust immunogens), to antibody characterization (as the first structures generated more than 40 years ago were those of hapten binders), and enabled and expanded antibody engineering technologies. The latter field of engineered antibodies evolved over many years and many steps resulting in recombinant humanized or human‐derived antibody derivatives in multiple formats. Today, hapten‐binding antibodies are applied not only as reagents and tools (where they still play an important part) but evolved also to engineered targeting and pretargeting vehicles for disease diagnosis and therapy. Here we describe recent applications of hapten‐binding antibodies and of engineered mono‐ and bispecific hapten‐binding antibody derivatives. We have designed and applied these molecules for the modulation of the pharmacokinetic properties of small compounds or peptides. They are also integrated as additional binding entities into bispecific antibody formats. Here they serve as non‐covalent or covalent coupling modules to haptenylated compounds, to enable targeted payload delivery to disease tissues or cells.